On thermal instability of Kuvshiniski fluid with suspended particles saturated in a porous medium in the presence of a magnetic field - Singh, Mahinder (Zielona Góra: Uniwersytet Zielonogórski)
The thermal instability of a Kuvshiniski viscoelastic fluid is considered to include the effects of a uniform horizontal magnetic field, suspended particles saturated in a porous medium. The analysis is carried out within the framework of the linear stability theory and normal mode technique. For the case of stationary convection, the Kuvshiniski viscoelastic fluid behaves like a Newtonian fluid and the magnetic field has a stabilizing effect, whereas medium permeability and suspended particles are found to have a destabilizing effect on the system, oscillatory modes are introduced in the system, in the absence of these the principle of exchange of stabilities is valid. Graphs in each case have been plotted by giving numerical values to the parameters, depicting the stability characteristics. Sufficient conditions for the avoidance of overstability are also obtained.
Keywords: thermal convection; Kuvshiniski fluid; suspended particles; magnetic field; porous medium